SDN and NFV Security Security Analysis of Software-Defined Networking and Network Function Virtualization (Lecture Notes in Networks and Systems,, 2018)
This book provides security analyses of several Software Defined Networking (SDN) and Network Functions Virtualization (NFV) applications using Microsoft's threat modeling framework STRIDE. Before deploying new technologies in the production environment, their security aspects must be considered. Software Defined Networking (SDN) and Network Functions Virtualization (NFV) are two new technologies used to increase e.g. the manageability, security and flexibility of enterprise/production/cloud IT environments. Also featuring a wealth of diagrams to help illustrate the concepts discussed, the book is ideally suited as a guide for all IT security professionals, engineers, and researchers who need IT security recommendations on deploying SDN and NFV technologies. .